2009
DOI: 10.1016/j.virol.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A combination of defective DNA and protective host factors are found in a set of HIV-1 ancestral LTNPs

Abstract: We studied viral evolution in three HIV-1 ancestral patients from a group of LTNPs; although some minor sequences showing viral evolution were detected in all patients, the extremely low viral evolution of their viruses was shown by the phylogenetic analysis of the env sequences. Complete nucleotide sequencing of viral DNA showed the major presence of deletions. In two patients, deletions of 1088 and 228 nucleotides mapped to 5' LTR-gag region; in the other, a 247 nucleotide deletion was positioned in pol gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…In TP with RNA viral loads above 10,000 copies/mL, env gene diversity increases at a mean rate of 1%/year and reaches a peak (π = 6–10%) after 5–10 years post-infection [3]. High levels of env proviral diversity (π = 4-8%) have been also described in samples taken 10–15 years after HIV diagnosis from LTNPs with plasma viremia between 2000 and 10,000 copies/mL [4, 16, 17, 19, 45]. Much lower levels of env proviral diversity (π = 0.1–6%), by contrast, were detected here in samples taken between 5 and 20 years after HIV diagnosis from HIV controllers (RNA viral load lower than 2000 copies/mL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In TP with RNA viral loads above 10,000 copies/mL, env gene diversity increases at a mean rate of 1%/year and reaches a peak (π = 6–10%) after 5–10 years post-infection [3]. High levels of env proviral diversity (π = 4-8%) have been also described in samples taken 10–15 years after HIV diagnosis from LTNPs with plasma viremia between 2000 and 10,000 copies/mL [4, 16, 17, 19, 45]. Much lower levels of env proviral diversity (π = 0.1–6%), by contrast, were detected here in samples taken between 5 and 20 years after HIV diagnosis from HIV controllers (RNA viral load lower than 2000 copies/mL).…”
Section: Discussionmentioning
confidence: 99%
“…In some LTNPs, DNA proviral populations are composed of a complex mixture of archival (dating close to the patient’s seroconversion time) and recent (dating close to the sampling time) variants [13] and displayed no temporal structure in the changes of diversity and divergence during chronic infection [14]. In all chronically infected EC and some VC, DNA proviral populations are extremely homogenous (with less than 2% env diversity), mostly composed by ancestral sequences and with no measurable divergence over time [5, 9, 10, 12, 1519]. A recent study demonstrates that most proviral sequences detected in PBMC from HIV controllers are largely representative of archival variants probably integrated during primary infection and propagated by clonal expansion of the memory CD4 + T cell latent reservoir, although rare proviral clones of recent origin could be detected in some patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that virus strains from LTNPs are less evolved and thus less capable of evading the host immunological response when compared with progressor strains (Sandonís et al, 2009;Wang et al, 2003). The classic example of HIV-1 LTNP virus attenuation is the Sydney Blood Bank cohort (n58), whose members were infected from blood transfusions from the same donor infected with an HIV-1 strain that contained a large Mechanisms of control in HIV-1 LTNPs deletion in a long-terminal repeat from a conserved and biologically significant area in the nef gene (Crotti et al, 2006;Learmont et al, 1999).…”
Section: Ltnp Virus Attenuationmentioning
confidence: 99%
“…Analyses of HIV long-term nonprogressors (LTNPs) and elite controllers (ECs) suggest diverse and multifactorial mechanisms of natural control of viremia. Factors contributing to elite control (undetectable HIV viral load) may include attenuated viruses with slow viral evolution (19,20), although replication-defective viruses are by no means always present (21)(22)(23)(24). HLA-B*57-positive elite controllers maintained viral suppression despite the presence of escape mutations, with evidence of CTL responses against unmutated epitopes and de novo responses against epitopes with escape mutations (25)(26)(27).…”
mentioning
confidence: 99%